Violence Against Women In The Family - Andrić, Sanela D.; Milašinović, Srđan M. (Sociološki pregled, 2018)
Violence against women in the family is a problem aﬀecting our society in which the roots of patriarchy continue to be the source (of reproduction) of gender-based violence. The paper presents some of the domestic research on violence against women in the family in order to see which forms of violence they are targeting. Also, on the basis of secondary material, forms of psychological, emotional and economic violence are described, which victims of violence fnd more difcult to recognize and are thus not aware of being exposed to them. Based on the data of the Ministry of Interior of the Republic of Serbia, data on registered acts of domestic violence in the period from 2013 to 2017 are presented.Keywords: family violence, women